Identification of Mitochondrial DNA Polymorphism on Linezolid-induced Toxic Optic Neuropathy Patients - Setyorini, Dwi Indira; Ahmad, Zen; Amalia, Ella; Subandrate, Subandrate; Hutabarat, Yosafat Beltsazar (Universitas Islam Bandung, 2025)
Drug-resistant tuberculosis (DR-TB) is difficult to eradicate due to several factors, including insufficient treatment and medication side effects. Linezolid is among the medications with serious adverse effects. Linezolid toxicity is suspected to be related to the drug's binding to mitochondrial 16s rRNA. Some studies indicate that polymorphisms in patients' mtDNA may increase vulnerability to the development of toxic optic neuropathy. This study aims to identify a genetic influence on the vulnerability to the occurrence of toxic optic neuropathy side effects in drug-resistant tuberculosis patients receiving linezolid treatment. This research was conducted at the Faculty of Medicine, Universitas Sriwijaya, Palembang, from September to October 2023. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was undertaken to detect mutations in the G3010A mtDNA of the patients. Two patients experiencing toxic optic neuropathy side effects during drug-resistant tuberculosis treatment underwent blood sample collection. Blood samples were examined for mutations in the G3010A and A2706G genes using the PCR-RFLP method. The PCR-RFLP examination results indicated the presence of mutations in G3010A. In conclusion, polymorphism of G3010A mtDNA may contribute to the vulnerability to toxic optic neuropathy side effects in drug-resistant tuberculosis patients receiving linezolid. Further research with a larger population is needed to prove the involvement of mtDNA polymorphisms in the vulnerability to toxic optic neuropathy.